Use of the nematode Caenorhabditis elegans in toxicity tests in water samples from the Calera river, Ecuador - Pilaloa-Tamayo, Juan (2022)
The province of El Oro is the most important gold mining area in Ecuador, but the activity has caused damage to the ecosystem and human health, due to the dumping of extraction waste loaded with heavy metals into the Calera River, which is a tributary with the Yellow River of the Puyango river. This work presents the results of the evaluation of the toxicity of the water and sediments of the Calera River using the nematode Caenorhabditis elegans as a bioindicator for environmental monitoring. The quantification of heavy metals by atomic absorption spectroscopy in samples collected along the Calera River, both in water and in sediments, revealed that the concentration in water was below the permissible limits established by the Ecuadorian Environmental Standard, while in the sediment sample, the concentration values of heavy metals considerably exceeded the permissible limits, particularly Arsenic and Cadmium, which were the ones detected with the highest concentrations. In the bioassays with C. elegans subjected to different concentrations and exposure times of 12, 18, 24 and 36 hours, no mortality rate was detected in the water samples analyzed, which is attributed to the low concentration of heavy metals. The exposure of the nematodes to the sediment extracts, induced mortality in all the samples, mainly in those coming from the sector in which the rock material processing plants are located.